2017
DOI: 10.5005/jp-journals-10015-1453
|View full text |Cite
|
Sign up to set email alerts
|

Quantity Differences of Secondary Metabolites (Saponins, Tannins, and Flavonoids) from Binahong Plant Extract (Anredera cordifolia (Ten.) Steenis) treated and untreated with Colchicines that play a Role in Wound Healing

Abstract: Aim: The aim of this study is to compare whether there are differences in the value content of secondary metabolites (saponins, tannins, and flavonoids) between the group treated with Binahong leaves (administration of colchicines) and the group treated with Binahong leaves without the application of colchicines. Materials and methods:The design of this study is an experimental research laboratory study. This research was done in four different places in which colchicines were applied to improve the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…Likewise, saponins have also been reported to contain antibacterial properties [ 56 ]. Saponins from plant studies have been reported to enhance wound healing activity [ 57 , 58 ] and prevent excessive scar formation in experimental mice [ 59 ]. Triterpenoids are also phytochemicals, well known to have anti-inflammatory and antibacterial activities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, saponins have also been reported to contain antibacterial properties [ 56 ]. Saponins from plant studies have been reported to enhance wound healing activity [ 57 , 58 ] and prevent excessive scar formation in experimental mice [ 59 ]. Triterpenoids are also phytochemicals, well known to have anti-inflammatory and antibacterial activities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cells also cannot be formed again because tannins inhibit the DNA. 11 In addition there are terpenoids and alkaloids. The terpenoid compounds action mechanism is by damaging the outer membrane, inner membrane and can also interact with membrane proteins with the help of alkaloids by inhibiting the formation of enzymes (esterase, DNA-, RNA-polymerase), inhibiting cell respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloid merupakan senyawa yang mengandung paling sedikitnya 1 atom nitrogen dalam struktur cincin heterosiklik. Alkaloid pada family Basellaceae berperan sebagai antimikroba dan antioksidan (Ain et al, 2016;Hanafiah et al, 2017).…”
Section: Alkaloidunclassified